Adenoviral gene transfer of a single‐chain IL‐23 induces psoriatic arthritis–like symptoms in NOD mice. Issue 8 (6th June 2019) - Flores, Rafael R.; Carbo, Lana; Kim, Eun; Van Meter, Montina; De Padilla, Consuelo M. Lopez; Zhao, Jing; Colangelo, Debora; Yousefzadeh, Matthew J.; Angelini, Luise A.; Zhang, Lei; Pola, Enrico; Vo, Nam; et al.
ABSTRACT: Previously, we demonstrated that intratumoral delivery of adenoviral vector encoding single‐chain (sc) IL‐23 (Ad.scIL‐23) was able to induce systemic antitumor immunity. Here, we examined the role of IL‐23 in diabetes in nonobese diabetic mice. Intravenous delivery of Ad.scIL‐23 did not accelerate the onset of hyperglycemia but instead resulted in the development of psoriatic arthritis. Ad.scIL‐23–treated mice developed erythema, scales, and thickening of the skin, as well as intervertebral disc degeneration and extensive synovial hypertrophy and loss of articular cartilage in the knees. Immunological analysis revealed activation of conventional T helper type 17 cells and IL‐17–producing γδ T cells along with a significant depletion and suppression of T cells in the pancreatic lymph nodes. Furthermore, treatment with anti–IL‐17 antibody reduced joint and skin psoriatic arthritis pathologies. Thus, these Ad.scIL‐23–treated mice represent a physiologically relevant model of psoriatic arthritis for understanding disease progression and for testing therapeutic approaches.—Flores, R. R., Carbo, L., Kim, E., Van Meter, M., De Padilla, C. M. L., Zhao, J., Colangelo, D., Yousefzadeh, M. J., Angelini, L. A., Zhang, L., Pola, E., Vo, N., Evans, C. H., Gambotto, A., Niedernhofer, L. J., Robbins, P. D. Adenoviral gene transfer of a single‐chain IL‐23 induces psoriatic arthritis–like symptoms in NOD mice. FASEB J. 33, 9505–9515 (2019). www.fasebj.org